2008
DOI: 10.1021/tx800059j
|View full text |Cite
|
Sign up to set email alerts
|

2,2′,3,3′,6,6′-Hexachlorobiphenyl (PCB 136) Atropisomers Interact Enantioselectively with Hepatic Microsomal Cytochrome P450 Enzymes

Abstract: 2,2',3,3',6,6'-Hexachlorobiphenyl (PCB 136) is a chiral and highly neurotoxic PCB congener of environmental relevance. (+)-PCB 136 was previously shown to be enriched in tissues from mice treated with racemic PCB 136. We investigated the spectral interactions of (+)-, (-)-, and (+/-)-PCB 136 with mouse and rat hepatic microsomal cytochrome P450 (P450) enzymes to test the hypothesis that enantioselective binding to specific P450 enzymes causes the enrichment of (+)-PCB 136 in vivo. Hepatic microsomes prepared f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
85
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(89 citation statements)
references
References 52 publications
(80 reference statements)
2
85
1
1
Order By: Relevance
“…Male and female C57BL/6 mice (7-8 weeks) were obtained from the Jackson Laboratory (Bar Harbor, ME) and randomly assigned to one of four groups: 1) phenobarbital (PB; Sigma-Aldrich, St. Louis, MO) at 102 mg/kg/day in saline or 2) saline at 20 ml/kg/day, i.p., for 3 consecutive days; 3) dexamethasone (DEX; Sigma-Aldrich) at 50 mg/kg/day in corn oil (CO) or 4) CO (Fisher Scientific, Pittsburg, PA) at 10 ml/kg/day, i.p., for 4 consecutive days (KaniaKorwel et al, 2008). Male Sprague-Dawley rats (8 weeks) were purchased from Harlan, Inc. (Indianapolis, IN), acclimated for 1 week, then randomly assigned to one of four groups: 1) PB at 102 mg/kg/day in saline or 2) saline at 5 ml/kg/day, i.p., for 3 consecutive days; 3) DEX at 50 mg/kg/day in CO or 4) CO vehicle control at 5 ml/kg/day, i.p., for 4 consecutive days (Kania-Korwel et al, 2008). Animals were euthanized 24 hours after the last treatment by CO 2 asphyxiation followed by cervical dislocation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Male and female C57BL/6 mice (7-8 weeks) were obtained from the Jackson Laboratory (Bar Harbor, ME) and randomly assigned to one of four groups: 1) phenobarbital (PB; Sigma-Aldrich, St. Louis, MO) at 102 mg/kg/day in saline or 2) saline at 20 ml/kg/day, i.p., for 3 consecutive days; 3) dexamethasone (DEX; Sigma-Aldrich) at 50 mg/kg/day in corn oil (CO) or 4) CO (Fisher Scientific, Pittsburg, PA) at 10 ml/kg/day, i.p., for 4 consecutive days (KaniaKorwel et al, 2008). Male Sprague-Dawley rats (8 weeks) were purchased from Harlan, Inc. (Indianapolis, IN), acclimated for 1 week, then randomly assigned to one of four groups: 1) PB at 102 mg/kg/day in saline or 2) saline at 5 ml/kg/day, i.p., for 3 consecutive days; 3) DEX at 50 mg/kg/day in CO or 4) CO vehicle control at 5 ml/kg/day, i.p., for 4 consecutive days (Kania-Korwel et al, 2008). Animals were euthanized 24 hours after the last treatment by CO 2 asphyxiation followed by cervical dislocation.…”
Section: Methodsmentioning
confidence: 99%
“…We also assessed the influence of sex and species on P450 expression profiles in the brain using the male mouse as the reference. We studied CYP2B (mouse CYP2B10/rat CYP2B1/2), CYP3A (mouse CYP3A11/rat CYP3A2), and CYP1A2 because these isoforms have been implicated in the metabolism of polychlorinated biphenyls (Kania-Korwel et al, 2008Curran et al, 2011), polybrominated diphenyl ethers (Erratico et al, 2013;Feo et al, 2013), and organophosphorus pesticides (Tang et al, 2001;Foxenberg et al, 2007). Two orphan P450s, CYP4X1 and CYP2S1 (Guengerich et al, 2010), were also included in this study because s This article has supplemental material available at dmd.aspetjournals.org.…”
mentioning
confidence: 99%
“…The individual enantiomers of chiral compounds can interact enantioselectively with enzymes and biological receptors in organisms. 5,26 For example, Kania-Korwel et al 27 found a greater binding of (+)-PCB 136 to P450 isozymes CYP2B and CYP3A than (−)-PCB 136 in mouse and rat in vivo. The (−)-o,p,-DDT enantiomer was found to be an active estrogen mimic at the human estrogen receptor, whereas (+)-o,p,-DDT had negligible activity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In vitro experiments showed that (þ)-PCB 136 bound more strongly to mouse CYP isozymes than (À)-PCB 136 [277]. Binding was inhibited by CYP2B antibodies, indicating that CYP2B isozymes were involved [277]. However, enantioselectivity of PCBs did not change in mice exposed in vivo to CYP2B or CYP3A inducers [278], indicating that enantioselective bioprocessing of PCBs was not due solely to CYP-mediated biotransformation.…”
Section: Pcbsmentioning
confidence: 98%
“…In female mice, enrichment of (þ)-PCB 136 decreased with increasing dose (2-50 mg/kg body weight) of the racemate, suggesting a saturation of the enantioselective processes in the mice [276]. In vitro experiments showed that (þ)-PCB 136 bound more strongly to mouse CYP isozymes than (À)-PCB 136 [277]. Binding was inhibited by CYP2B antibodies, indicating that CYP2B isozymes were involved [277].…”
Section: Pcbsmentioning
confidence: 99%